An Overview Of Acute Lymphoid Leukemia (All) In A Dog - Mugale, Madhav; Lakra, Praggaya Priya; Chauhan, Vikash Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Acute lymphocytic leukemia (ALL, also known as acute lymphoblastic leukemia, or acute lymphoid leukemia) is a proliferation of undifferentiated lymphocytes and is the most common cancer Leukemias are malignant neoplasms of hematopoietic stem cells arising in the bone marrow (Nelson and Couto, 1998). The prognosis with chemotherapy treatment is poor in canine and feline patients, and the average survival time is only a few months. If left untreated, the estimated survival time from diagnosis is less than two weeks (Waikart et al., 2007). ALL can occur at any age in animals, although it is more prevalent in young and middle-age populations (Meuten, 2002).